Cultura alimentar “Rio Abaixo”: o impacto da poluição das águas nos hábitos alimentares tradicionais de soberania alimentar da comunidade São Pedro, Abaetetuba-PA - SILVA, Luiz Renan Ramos da (2020)
The research has as a spatial cut the “São Pedro” riverside community, in Abaetetuba-PA, which has been suffering from the influences of environmental impacts of companies and marine cargo accidents around it, thus reaching the food sovereignty of the community, since these need water for their cultivars, meeting their vital and physiological needs, and food, but face a constraint on this increasingly contaminated natural resource. In this context, the present work aimed to document the impacts of the low river water pollution in Abaetetuba - PA that affect the São Pedro community, due to the great influences of environmental impacts and affecting food sovereignty. For data collection, participatory observation was made with semi-structured interviews in the form of questionnaires, photographic records and the use of geoprocessing for map production. The main community is to cultivate cassava, but intercropped in the form of agroforestry yard with coffee, corn and kale, in addition to fishing and shrimp harvesting, but they are exploited subsistence resources that have been suffering yield changes due to impacts on the river. Water has a symbolic value and certainly without it and of good quality the community will not live, in this sense there is need for urgent active public policy intervention that enables the community population to experience the use of this fundamental natural resource for life.